How Academic Background Influences The Use of Language on Twitter: A Study of Post-Pandemic Discourse - Hanisah Hanafi; Abdul Hafid; Jefriyanto Saud (AMCA Journal of Community Development, 2025)
This research explores the variations in language register between lecturers and students on Twitter within the post-pandemic academic discourse context. Employing Biber and Conrad's theory of register, genre, and style as a guiding framework, the study analyzes tweets to unveil distinct linguistic features associated with the social roles of educators and learners. Lecturer tweets exhibit a supportive and motivational language style, aligning with their role as facilitators of learning and experts in their field. Student tweets, on the other hand, express frustrations, financial concerns, and societal critique, reflecting the impacts of the broader context of the pandemic on education and personal experiences. The analysis draws on sociolinguistic theories, critical discourse analysis, and genre analysis to interpret the linguistic choices made by both groups. The findings underscore the dynamic relationship between language use and social roles on Twitter, providing insights into how educators and students articulate experiences and challenges within the digital academic community in the post-pandemic era. Future research opportunities include exploring language evolution over time, analyzing engagement dynamics on social media platforms, and investigating regional language variations in academic discourse. Ultimately, this study contributes to the understanding of language use in online academic settings, emphasizing the intricate interplay between language, social roles, and contextual factors within digital communication landscapes.